(untitled) (Global Journal of Human-Social Science, 2024)
Describing in our present study presupposes the exploitation of a new didactic support in French in the college Cycle, the documentary Film in the learning process. Our objective is to improve French among our learners in their communications by describing in a foreign language which is French.